PEMBERDAYAAN PEREMPUAN MELALUI EKONOMI KREATIF : STUDI KASUS PEMILIK MAHACINTA JEWELRY DI PEKANBARU - Yetty Zahra Roihani; Firdaus Yusrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
Women's empowerment through the creative economy is an effort to improve women's welfare and independence through the process of utilizing existing resources to create creative business opportunities for MSMEs. However, in its implementation, it still faces obstacles in gender equality in the form of discrimination from the immediate environment and being underestimated by the social environment. This study aims to determine how the process of women's empowerment is carried out in the creative business of MSME Mahacinta Jewelry. This study uses a descriptive qualitative method approach with data collection techniques of observation, interviews, and field documentation. The results show that the owner of Mahacinta Jewelry has strong abilities in terms of creativity, jewelry design skills, and the ability to manage a business that has a positive influence on other women involved in the process. The owner of Mahacinta Jewelry also provides various resources that can be utilized. The empowerment process is carried out through informal training, task distribution, and direct guidance. This opens up broad opportunities for women to engage in creative economic activities. These opportunities are seen from the opportunity to become production partners, sell products independently, or learn new skills to increase income. Overall, the results of this study show that the empowerment process is carried out sustainably and is able to increase women's skills and income, but also provides space for them to dare to take a bigger role in economic and social life. Keywords: Women's Empowerment, Creative Economy, MSMEs, Women's Entrepreneurship, Mahacinta Jewelry